TRANSFORMASI PELAYANAN PUBLIK DAN DAMPAKNYA TERHADAP KEPUASAN MASYARAKAT PADA KANTOR CAMAT TUAH MADANI - Nova Syafrina (Eko dan Bisnis: Riau Economic and Business Review, 2026)
Abstract: This study aims to determine the effect of service quality on public satisfaction at the Tuah Madani Sub-district Office, Pekanbaru City. The population in this study were all residents who received services at the Tuah Madani Sub-district Office with a sample of 96 respondents determined using the Accidental Sampling technique. The research method used was a descriptive method with a quantitative approach. The results of the descriptive analysis showed that the majority of respondents gave a positive assessment of service quality and public satisfaction. In the service quality variable, 89% of respondents stated they agreed and strongly agreed, while in the public satisfaction variable, 86% of respondents stated they agreed and strongly agreed. Data analysis using simple linear regression produced the equation Y = 2.254 + 1.127X which indicated a positive relationship between service quality and public satisfaction. Based on the results of the t-test, the t-count value was 21.534, which was greater than the t-table of 1.660 with a significance level of 0.000, which was less than 0.05. This indicates that service quality has a positive and significant effect on public satisfaction at the Tuah Madani Sub-district Office, Pekanbaru City. The coefficient of determination (R²) value of 0.831 or 83.1% shows that service quality is able to explain variations in public satisfaction by 83.1%, while the remaining 16.9% is influenced by other factors not examined in this study.